2018
DOI: 10.1556/0806.46.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Detection and discrimination of barley- and wheat-specific forms of Wheat dwarf virus in Poland

Abstract: Wheat dwarf virus (WDV) is one of the most common viruses on cereal crops in Poland. Studies were undertaken aiming at molecular characterization of Polish isolates of the virus. The presence of two main groups, WDV-barley-and WDV-wheat-specific forms, in field samples has been confirmed. Detection and differentiation of WDV isolates was conducted using immuno-capture polymerase chain reactions. The studies were carried out on a set of 68 samples collected from different parts of the country. Obtained results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
4
3
0
Order By: Relevance
“…In Poland WDV was found for the first time in 1999 (Jeżewska 2001). The next studies confirmed WDV infections of wheat, barley and triticale plants in different parts of Poland (Jeżewska et al 2010) as well as the presence of both WDV-B and WDV-W forms (Trzmiel 2018).…”
Section: Rna Isolationsupporting
confidence: 65%
See 2 more Smart Citations
“…In Poland WDV was found for the first time in 1999 (Jeżewska 2001). The next studies confirmed WDV infections of wheat, barley and triticale plants in different parts of Poland (Jeżewska et al 2010) as well as the presence of both WDV-B and WDV-W forms (Trzmiel 2018).…”
Section: Rna Isolationsupporting
confidence: 65%
“…The results presented herein revealed the common presence of BYDV-SGV in tested samples. Our data, in comparison to a previous report (Trzmiel 2017) (Trzmiel 2018). Moreover, in 2015 when an outbreak of BYD on winter wheat and barley was observed, mixed infection of BYDV-MAV or BYDV-PAV and WDV was common but the rate of WDV infection was definitely lower (Trzmiel 2018).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…WDV population can be clearly divided into barley and wheat forms [ 3 , 6 , 10 , 14 ]. The genomes of these two forms share 84% nucleotide sequence identity however the CP gene is one of the most stable coding regions [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The comparative analysis of this region revealed ca. 83% nucleotide sequence identity between different barley- and wheat- infecting WDV isolates whereas up to 98% within the particular group [ 14 , 21 ]. Taking into account the genetic diversity of the WDV population, the primers for the LAMP assay were designed based on the alignment of CP sequences.…”
Section: Resultsmentioning
confidence: 99%